Multiple strategies for the treatment of invasive breast carcinoma: A comprehensive prospective. Issue 2 (February 2022) - Agarwal, Shivangi; Sau, Samaresh; Iyer, Arun K.; Dixit, Anshuman; Kashaw, Sushil K.
Graphical abstract: Highlights: The review offers comprehensive updated information on breast cancer therapeutics. For the last ten years, the potential therapeutic chemical scaffolds have been reviewed. Clinically approved antibodies and ADCs against HER-2 and TNBC have been discussed. The emerging therapeutic peptides against breast cancer have been appraised. The review summarizes the breast cancer vaccines under clinical evaluation. Abstract : In this review, we emphasize on evolving therapeutic strategies and advances in the treatment of breast cancer (BC). This includes small-molecule inhibitors under preclinical and clinical investigation, phytoconstituents with antiproliferative potential, targeted therapies as antibodies and antibody–drug conjugates (ADCs), vaccines as immunotherapeutic agents and peptides as a novel approach inhibiting the interaction of oncogenic proteins. We provide an update of molecules under different phases of clinical investigation which aid in the identification of loopholes or shortcomings that can be overcomed with future breast cancer research.